2018
DOI: 10.15406/mojes.2018.03.00098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lead on plants in terms of growing and biochemical parameters: a review

Abstract: Contamination of soil and water by various heavy metals such as lead, silver and cadmium is increasing day by day as result of different activities, such as industrialization and urbanization. Lead (Pb) is an example of potential heavy metal that is neither essential element nor have any role in the process of cell metabolism but is easily absorbed and accumulated in different parts of a plant. The lead uptake is mainly regulated by PH, particle size, and cation exchange capacity of the soil, root exudation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 45 publications
(49 reference statements)
0
25
0
Order By: Relevance
“…Pb accumulation in plants causes physiological problems, such as DNA damage and destroying root and shoot systems [114], and affects the enzymatic activities [115]. The effect of Pb toxicity on plants was studied by Nas et al [116]. The results indicated that a high concentration of Pb affected the fresh biomass and plant growth.…”
Section: Effect Of Lead Toxicity On Plantmentioning
confidence: 99%
“…Pb accumulation in plants causes physiological problems, such as DNA damage and destroying root and shoot systems [114], and affects the enzymatic activities [115]. The effect of Pb toxicity on plants was studied by Nas et al [116]. The results indicated that a high concentration of Pb affected the fresh biomass and plant growth.…”
Section: Effect Of Lead Toxicity On Plantmentioning
confidence: 99%
“…Lead is non-essential heavy metal and its accumulation in body at an elevated level and can causes headache, anaemia, damage of brain and central nervous system (Nas and Ali, 2018). Lead contents in present investigation were found in the range of 1.17 to 1.79 mg/kg.…”
Section: Leadmentioning
confidence: 46%
“…Under laboratory conditions, Jelea et al (2015) verified a reduction in germination with the increase in the concentration of lead nitrate. The decrease in the percentage of germination may be related to the interference of the metal in the activity of amylases and proteases (Nas and Ali, 2018;Boi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%